Public policy on the prevention of subsequent adolescent pregnancy: what type of policy prevails? - Fátima Estrada; Irma Romero-Pérez; Lourdes Campero; Celia Hubert; Aremis Villalobos (Cadernos de Saúde Pública, 2022)
This study aims to conduct a search of public-policy instruments seeking explicit references to subsequent adolescent pregnancy, as well as to discern what kinds of actions have been proposed as part of the international and national agendas to facilitate subsequent adolescent pregnancy prevention and care. During June 2021, we used an integrative review to search and to analyze national and international public policy instruments along with other documents related to subsequent adolescent pregnancy. We observed, for each, the presence of statements on subsequent adolescent pregnancy. The research team was then divided into triads to discuss and to classify each reference under one of the following categories: (a) a symbolic statement, that is, an intention not implying a specific action but rather presenting a vision for the future; (b) a substantive-material statement concerning an action intended to solve a problem; and (c) a procedural-material statement indicating specific actions, processes, budgets, and actors. We analyzed a total of 135 public-policy documents: 102 in Mexico and 33 internationally. Only four national and six international documents contained either symbolic or substantive-material references to the subject of interest and only one specified a procedural-material statement. The prevention and care of subsequent adolescent pregnancy are addressed only secondarily on the public agendas. Only a minimal number of actions comprise specific and standardized measures to prevent subsequent adolescent pregnancy according to the different actors involved. Designing a greater number of procedural-material policies will help to reduce morbidity and mortality in the mother-child binomial and promote a comprehensive development of this population.